The impact of social capital spatial structure and village collective action participation on farmland conservation behavior among farmers: evidence from three provinces of Northwest China - Xinjie Li; Qian Lu (Cogent Food & Agriculture)
This research employs micro-survey data from farmers across three provinces in Northwest China and utilizes an endogenous switching probit model to explore the effects of social capital’s spatial structure and village collective action participation on farmland conservation practices. The findings reveal that both embedded and disembedded forms of social capital exert a significant impact on farmland conservation efforts, either by amplifying or diminishing the effectiveness of village collective action participation. This research demonstrates that embedded social capital notably enhances farmers’ inclination to conserve farmland, whereas disembedded social capital exhibits a contrary influence; furthermore, participation in village collective actions significantly bolsters conservation efforts among farmers. Specifically, embedded social capital intensifies the positive impact of village collective action participation on conservation practices, while disembedded social capital mitigates it. The conclusions obtained after the robustness test still hold true. Counterfactual analysis reveals that if farmers who have not previously participated in village collective actions were to do so, their likelihood of adopting farmland conservation practices would increase by 15.8%. This finding is consistent across various matching methods, underscoring the robustness of the results. The impact of participation in village collective actions on farmland conservation behaviors varies significantly among farmer groups with different levels of endowment.